Introduction to epidemiology : distribution and determinants of disease in humans - Macera, Caroline A.; Shaffer, Richard A.; Shaffer, Peggy M. (Clifton Park, N.Y. : Cengage Learning, Inc, 2012)
"Introduction to Epidemiology: Distribution and Determination in Humans, the first offering in the Public Health Basics series, is an ideal introductory text designed for the student with little or no experience in epidemiology. Effective chapter organization allows you to first understand the basic concepts in epidemology such as its history and integration into public health, disease occurrence, data sources, accuracy, and study design. The second collection of chapters seamlessly guides you through the distribution and determinants of disease in humans--including cancer, diabetes, infectious diseases-- and the diseases of developing countries. This promises to be your go-to resource in navigating the complex data behind the spread of disease and its future prevention."--P. 4 of cover.
"Delmar Health Care"--Cover.
Includes bibliographical references and index.
Keywords: Epidemiology; Epidemiology